2012
DOI: 10.1175/jcli-d-11-00317.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Local and Remote Biophysical Effects of Afforestation over the Southeast United States in Boreal Summer*

Abstract: Afforestation has been proposed as a climate change mitigation strategy by sequestrating atmospheric carbon dioxide. With the goal of increasing carbon sequestration, a Congressional project has been planned to afforest about 18 million acres by 2020 in the Southeast United States (SEUS), the Great Lake states, and the Corn Belt states. However, biophysical feedbacks of afforestation have the potential to counter the beneficial climatic consequences of carbon sequestration. To assess the potential biophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 53 publications
(66 reference statements)
0
29
0
1
Order By: Relevance
“…Simulations were run on a 1.9 • × 2.5 • horizontal resolution for 30 years to allow the system to reach a dynamic equilibrium. While the simulations predicted climate over the entire globe, we focused our analysis on the grid-cells highlighted in Figure 1 and on the final 20 years of each simulation, discarding the first 10 years of simulation data as the model spin-up necessary to ensure that the climate has stabilized with the modified land surface (as commonly done in simulations focused on equilibrium differences in climate; [17,18]). We analyzed the responses of the 2-m air temperature variable simulated by the CESM because it is commonly reported in other modeling studies (e.g., [18]) and from meteorological stations in differing land-cover types [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations were run on a 1.9 • × 2.5 • horizontal resolution for 30 years to allow the system to reach a dynamic equilibrium. While the simulations predicted climate over the entire globe, we focused our analysis on the grid-cells highlighted in Figure 1 and on the final 20 years of each simulation, discarding the first 10 years of simulation data as the model spin-up necessary to ensure that the climate has stabilized with the modified land surface (as commonly done in simulations focused on equilibrium differences in climate; [17,18]). We analyzed the responses of the 2-m air temperature variable simulated by the CESM because it is commonly reported in other modeling studies (e.g., [18]) and from meteorological stations in differing land-cover types [21].…”
Section: Methodsmentioning
confidence: 99%
“…Simulation studies also allow for the assessment of temperature changes that include the final outcome of the interactions and feedback between the surface and atmosphere. Earth System Model modeling is a key tool for the development of a more refined understanding of the drivers governing the role of afforestation in the climate system [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is expected that LULCC would modify the existing nature of land-surfaceatmosphere interactions and, consequently, weather and climate. Many local-, regional-, and globalscale studies have demonstrated this assertion (e.g., Chase et al 2000;Chen et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, more and more scientists are focusing on the impacts of changes in vegetation cover on global and regional climate [1][2][3][4][5][6]. Vegetation affects climate mostly through albedo, evapotranspiration and surface roughness [7][8][9][10]. Charney [7] speculated overgrazing in the Sahel of Africa could lead to a loss of vegetation, which raises the surface albedo and cools the ground, so subsidence airflow continues and droughts increase in intensity.…”
mentioning
confidence: 99%
“…Also, a reduction in evapotranspiration leads to decreased precipitation and a slowing of the hydrological cycle. Cheng et al [9] found an increase in the density of forest cover increase the surface roughness and induces convergence, so the anomalous ascent increases cloud cover and precipitation. Also, the ways in which vegetation affects climate may vary by latitudes [10][11][12].…”
mentioning
confidence: 99%